The structural-energy state of metal nanopowders and the problems of certifying them - Ilyin A. P. Aleksandr Petrovich; Shuvalov G. V.; Klekovkin I. V.; Korshunov A. V. Andrey Vladimirovich; Tolbanova L. O. Lyudmila Olegovna (2009, 2009)
The basic characteristics of metal nanopowders, namely, the shape, particle sizes, the metal componentcontent, the chemical activity parameters, the electrochemical characteristics, and the thermodynamicstate of the nanoparticles and nanopowders, are considered. Experimental results are presented on the useof standard methods of analysis and the features of their use when determining the above characteristics.It is shown that, for certifying nanopowders as metastable systems, a whole range of methods of analysisis required.